Bacillus amyloliquefaciens Ameliorates Dextran Sulfate Sodium-Induced Colitis by Improving Gut Microbial Dysbiosis in Mice Model - Cao, Guangtian; Wang, Kangli; Li, Zhanming; Tao, Fei; Xu, Yinglei; Lan, Junhong; Chen, Guangyong; Yang, Caimei (Frontiers in Microbiology, 2019)
Several species of Bacillus exert beneficial effects on the maintenance of intestinal homeostasis and host health. However, whether Bacillus amyloliquefaciens (BA) can improve gut microbial dysbiosis and ameliorate colitis is unknown. Therefore, we conducted the present study to investigate the effects of BA administration on intestinal morphology, inflammatory response, and microbial composition in a mouse model of dextran sulfate sodium (DSS)-induced colitis. The results showed that BA administration significantly ameliorated body weight loss and decreased disease activity index and impaired colonic tissue morphology in DSS-treated mice. In addition, levels of immunoglobulins, as well as pro-inflammatory cytokines, were decreased after BA administration. Importantly, gut microbiota profiling indicated difference in beta-diversity between BA-administrated and DSS-treated mice, according to weighted PCoA results. The abundance of the Firmicutes genus was increased, whereas that of Bacteroidetes was decreased following BA administration. Furthermore, PICRUSt analysis showed that the most significantly changed pathways between the two groups of mice were carbohydrate, lipid, and amino acid metabolism. In conclusion, our results showed that BA administration has beneficial effects on DSS-induced colitis, suggesting that this strategy might be useful for the treatment of dysbiosis during ulcerative colitis. Further, the changes in metabolism, especially amino acid metabolism, might contribute to the beneficial effects of BA on the amelioration of DSS-induced colitis.